Ascent to civilization : the archaeology of early man - Gowlett, John. (New York : Distributed by Random House, 1984)
Details the discoveries about early man and his life.
Includes index.
Bibliography: p. 203-204.
Young Adult.
Keywords: Civilization -- History; Man, Prehistoric; Social evolution; Civilization -- History; Fossil hominids; Prehistoric peoples; Social change